2019
DOI: 10.12691/ajfn-6-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenized Water Effects on Protection of Brain Cells from Oxidative Stress and Glutamate Toxicity

Abstract: Hydrogenized water is known to have protective effects on cells and tissues, mainly through its antioxidant activities. Here we examined the protective effects of a commercial source of hydrogenized water on cultured human brain cells. Hydrogenized water was able to protect brain cells from oxidative stress and glutamate toxicity. At H 2 concentrations above 0.01 mM the glutathione levels increased in cultured brain cells. The level of glutathione rose from approximately 500 to approximately 850 μM at the maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In the brain, glutathione is only presented in millimolar concentrations, and thus makes this organ prone to oxidative damage compared to other tissues in the body (Settineri et al, 2018 ). A disruption in glutathione homeostasis could induce oxidative stress and lead to neurodegenerative diseases including Parkinson's disease (Mischley et al, 2013 ), Alzheimer's disease (Braidy et al, 2015 ), and dementia (Duffy et al, 2015 ) which impaired motor and cognitive functions.…”
Section: Role Of Antioxidants In the Prevention Of Age-related Diseasmentioning
confidence: 99%
“…In the brain, glutathione is only presented in millimolar concentrations, and thus makes this organ prone to oxidative damage compared to other tissues in the body (Settineri et al, 2018 ). A disruption in glutathione homeostasis could induce oxidative stress and lead to neurodegenerative diseases including Parkinson's disease (Mischley et al, 2013 ), Alzheimer's disease (Braidy et al, 2015 ), and dementia (Duffy et al, 2015 ) which impaired motor and cognitive functions.…”
Section: Role Of Antioxidants In the Prevention Of Age-related Diseasmentioning
confidence: 99%
“…It has been found that Nrf2 is upregulated by ingestion of hydrogen-rich water. The researchers found an "increased Nrf2 activation response" (Settineri et al, 2018).…”
Section: Free Radical Theory Of Agingmentioning
confidence: 99%
“…A recently published study has shown cell-protective effects by hydrogen administration in central nervous system diseases caused by oxidative stress. The researchers have found an increase in glutathione synthesis caused by hydrogen-mediated gene expression (Settineri et al, 2018).…”
Section: Brain and Nerve Diseasesmentioning
confidence: 99%